Urea Azines (Bisguanidines): Electronic Structure, Redox Properties, and Coordination Chemistry. Issue 13 (8th April 2015) - Herrmann, Hendrik; Reinmuth, Matthias; Wiesner, Sven; Hübner, Olaf; Kaifer, Elisabeth; Wadepohl, Hubert; Himmel, Hans‐Jörg
Abstract: Urea azines are a largely neglected class of compounds. We show herein that they can easily be synthesized and sublimed at higher temperatures (90–100 °C) without decomposition. Our discussion includes the derivatives N, N′ ‐diisopropylurea azine (2 ), tetramethylurea azine (3 ), and N, N′ ‐dimethylethyleneurea azine (4 ) as examples. Vibrational spectroscopy and quantum chemical calculations were used to study their electronic structure in detail. A clear trend in the calculated decomposition to N2 and carbene is found, but the analysis reveals that this trend reflects the stability of the carbene decomposition product rather than changes in the electronic structure of the urea azines. Using cyclic voltammetry (CV) measurements we show that the urea azines are strong organic electron donors, which can be oxidized reversibly in two well‐separated one‐electron steps. The radical salt4 (TCNQ), featuring radical monocations and radical monoanions, which form mixed stacks in the solid state, was prepared by reaction of neutral4 with tetracyanoquinodimethane (TCNQ). Oxidation of4 with silver salts Ag + X – (X = BF4 or PF6 ) was accompanied by dehydrogenation, leading to intensively red‐brown colored radical azoimidazolium dyes. Furthermore, urea azines were used as chelating ligands. In the case of2, coordination to late transition metals initiates tautomerization. Reaction of2 with boron hydrides leads to hydrogen elimination and formation of new B, N bi‐heterocyclic ring structures. Abstract : Electron donors: This article analyses the electronic structure of urea azines and shows that they are strong organic electron donors and redox‐active ligands.